The Impact of Electoral Systems on Government Formation and Stability in Developing Countries: Selected Models: international and political journal - Fadhil , Assist lecturer Huayda Abbas (The International and Political Journal, 2025)
This research presents a comparative study of three Arab developing countries Iraq, Algeria, and Egypt to analyze the impact of electoral systems on government formation and political stability. The study explores the legal and historical background of each electoral system, the mechanisms of forming executive power, as well as, the level of political stability resulting from each system within its national context. The findings of the study reveal that the electoral systems in developing countries influence not only the type of political representation but also the overall stability of governments. In Iraq, proportional representation ensured inclusiveness but led to fragile coalition governments. In Algeria, the closed-list proportional system provided apparent stability under a dominant ruling party. Egypt experienced multiple electoral reforms that produced varying patterns of representation and stability, shifting from pluralism to authoritarian consolidation. The study concludes that the effectiveness of electoral systems in supporting stable governance depends on their design and compatibility with the political and social context. It recommends adopting mixed systems that balance representation with governability and fostering a culture of political consensus.